Breastfeeding and behavior disorders among children and adolescents: a systematic review - Wanêssa Lacerda Poton; Ana Luiza Gonçalves Soares; Elizabete Regina Araújo de Oliveira; Helen Gonçalves (Universidade de São Paulo, 2018)
ABSTRACT OBJECTIVE This systematic review study aimed to assess the evidence available for the association between breastfeeding and behavior disorders in childhood and adolescence. METHODS The search was carried out in the PubMed, Lilacs, and PsycINFO databases up to December 2016. Inclusion criteria were as follows: prospective, retrospective and cross-sectional studies assessing the association between breastfeeding and behavior disorders in childhood or adolescence, using psychometric tests, carried out in humans and published in Portuguese, English, or Spanish. The search was performed in several stages by two independent researchers using pre-established criteria. RESULTS Eighteen studies met the inclusion criteria. Breastfeeding for a period equal to or higher than three or four months seemed to be inversely associated with total behavior and conduct disorders in childhood; however, the association remains unclear for other behavior disorders. Only four studies assessed behavior disorders in adolescence, and when an association was found, it was likely to be positive. The duration of breastfeeding seemed to be more important than the exclusive or non-exclusive pattern of breastfeeding. CONCLUSIONS Breastfed children for at least three to four months had fewer total behavior and conduct disorders in childhood. Further studies are needed to better understand this association, particularly in adolescence and involving other behavioral profiles.